Evaluation of the Implementation of Safety Standards in the Debarkation and Embarkation Process of Seatoll Vessel R-72 at Anchorage - Fadel Muhammad; Muhammad Idris; Idham Dwi Satria; Filemon Filemon; Muhammad Sapril Siregar; Stevian G. A. Rakka (Dinasti International Journal of Education Management and Social Science, 2025)
This study aims to evaluate the implementation of safety standards in the debarkation and embarkation process of the R-72 seatoll vessel at anchorage in Sofyanin Village. The research employed a qualitative case study design, utilizing field observations, interviews, questionnaires, and literature review. The findings indicate that passenger safety is influenced by three main dimensions: structural–policy, operational, and cultural. Structurally, the absence of a permanent pier and lack of regulatory oversight are the dominant factors increasing risks. Operationally, the captain’s ability to determine anchorage points and the limited availability of safety equipment serve as critical challenges. Culturally, low public awareness of safety procedures further exacerbates vulnerabilities. Evaluation against international standards (SOLAS, STCW, ISM Code, LSA Code) and national regulations (Law No. 17/2008, MoT Regulation No. 11/2023) reveals significant gaps between requirements and actual practices. The risk matrix analysis shows that most hazards, such as passengers falling overboard, capsizing of small transfer boats, and injuries from gangways, fall under the High–Extreme category. Therefore, this study recommends strengthening regulatory oversight, providing safety facilities in compliance with standards, and promoting safety culture awareness among local communities to minimize maritime accident risks.